Biological activity and metabolite profiling of marine sponges and characterization of bioactive compounds isolated from Haliclona sp. - Lee, Kah Nyan (2019)
Marine natural products, especially sponges, are the primary producers of secondary metabolites that of interest for investigation for clinical applications globally. However, there are limited studies being performed on sponges from Malaysia waters. Hence, the current study aimed to screen and isolate bioactive metabolites from marine sponges (Haliclona, Xestospongia, Aaptos, Axinella, Axinyssa, Mycale, Plakortis, and Penares) of Malaysia waters. Preliminary studies focused on several biological activities [α-glucosidase, cytotoxicity, antioxidant potential, nitric oxide (NO) scavenging activity, and antimicrobial] from marine sponge samples collected from Langkawi Island and Port Dickson. The most active fraction were chosen for nuclear magnetic resonance (NMR) and liquid chromatography mass spectrometry (LCMS) profiling before proceeding with various chromatographic methods for isolation. The bioassay screening results showed that marine sponges from Langkawi Island displayed better activities with DPPH inhibition ranges from 0 to 81.89%, NO scavenging ranges from 0 to 83.82%, and IC50 values for cytotoxicity (against MCF- 7) ranging from 20.41 to 40.19 g/mL except for α-glucosidase inhibition testing which had inhibition ranges from 0 to 0.83%. However, the Port Dickson samples showed the highest inhibition among all the tested biological activities except for the NO scavenging. However, the other samples from Port Dickson showed inhibition ranges approximately 20 to 30% for DPPH and 30 to 40% for NO scavenging testing. Haliclona sp. (L2) from Langkawi Island was chosen for further fractionation and isolation due to its overall performance in the screening. Further bioassay testing on the L2 fractions found that the non-polar fractions [hexane (14.05% inhibition in α- glucosidase) and dichloromethane (DCM) (45.24% inhibition of DPPH and 94.66% inhibition of NO scavenging)] were the most active fractions. NMR profiling tentatively identified 43 metabolites including amines, amides, fatty acids and carboxylic acids from the Haliclona sp. crude extract and nine secondary metabolites from the hexane and DCM active fractions; the main fatty acids constituents included linolenic acid, palmitic acid and arachidic acid. Characterization of compounds such as tryptophan, indoleacrylic acid, nor-5β-cholestane-3α,7α,12α,24,25-pentol, adenylsuccinic acid, and muricatacin using LCMS were performed with supporting data from the literatures and MS database. Subsequently, compounds isolation was performed on the nonpolar fractions using various chromatographic methods, including column chromatography and high-performance liquid chromatography (HPLC). A cholestanol derivative (1) was isolated from the hexane fraction while 1- (phenoxyamino)undecan-4-ol (2) and 1-(phenoxyamino)dodecan-3-ol (3) were isolated from the DCM fraction. Characterization of the isolated compounds was successfully performed based on the collection of spectroscopic (IR, NMR and MS) data with comparisons to the literatures. In conclusion, the current study successfully assessed the bioactivity of 16 species from marine sponges collected from Malaysian waters and characterized isolated compounds from the nonpolar active fractions of Haliclona sp.. These findings are also useful and may serve as an important basis for future drug discovery and development from marine organisms.